Oceanographic controls on shallow‐water temperate carbonate sedimentation: Spencer Gulf, South Australia. Issue 1 (January 2016) - O'Connell, Laura G.; James, Noel P.; Doubell, Mark; Middleton, John F.; Luick, John; Currie, David R.; Bone, Yvonne
Abstract: Spencer Gulf is a large ( ca 22 000 km 2 ), shallow (<60 m water depth) embayment with active heterozoan carbonate sedimentation. Gulf waters are metahaline (salinities 39 to 47‰) and warm‐temperate ( ca 12 to −28°C) with inverse estuarine circulation. The integrated approach of facies analysis paired with high‐resolution, monthly oceanographic data sets is used to pinpoint controls on sedimentation patterns with more confidence than heretofore possible for temperate systems. Biofragments – mainly bivalves, benthic foraminifera, bryozoans, coralline algae and echinoids – accumulate in five benthic environments: luxuriant seagrass meadows, patchy seagrass sand flats, rhodolith pavements, open gravel/sand plains and muddy seafloors. The biotic diversity of Spencer Gulf is remarkably high, considering the elevated seawater salinities. Echinoids and coralline algae (traditionally considered stenohaline organisms) are ubiquitous. Euphotic zone depth is interpreted as the primary control on environmental distribution, whereas seawater salinity, temperature, hydrodynamics and nutrient availability are viewed as secondary controls. Luxuriant seagrass meadows with carbonate muddy sands dominate brightly lit seafloors where waters have relatively low nutrient concentrations ( ca 0 to 1 mg Chl‐a m −3 ). Low‐diversity bivalve‐dominated deposits occur in meadows with highest seawater salinities and temperatures (43 to 47‰, up to 28°C). Patchy seagrass sand flats cover less‐illuminated seafloors. Open gravel/sand plains contain coarse bivalve–bryozoan sediments, interpreted as subphotic deposits, in waters with near normal marine salinities and moderate trophic resources (0·5 to 1·6 mg Chl‐a m −3 ) to support diverse suspension feeders. Rhodolith pavements (coralline algal gravels) form where seagrass growth is arrested, either because of decreased water clarity due to elevated nutrients and associated phytoplankton growth (0·6 to 2 mg Chl‐a m −3 ), or bottom waters that are too energetic for seagrasses (currents up to 2 m sec −1 ). Muddy seafloors occur in low‐energy areas below the euphotic zone. The relationships between oceanographic influences and depositional patterns outlined in Spencer Gulf are valuable for environmental interpretations of other recent and ancient (particularly Neogene) high‐salinity and temperate carbonate systems worldwide.